TINJAUAN KONDISI FISIK ATLET TAEKWONDO PUTRA SMA NEGERI 1 PANGKALAN KERINCI - Yuliyah Khumayroh; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the extent of the level of physical condition of male male athletes in SMA 1 Pangkalan Kerinci in terms of durability, flexibility, speed, strength and agility. This research was carried out at the Pangkalan Kerinci Regent Office Creative Park field, Pelalawan Regency, Riau Province in November 2018 until June 2019. The population to be used was the Team of Men of Taekwondo Putra SMA 1 Pangkalan Kerinci consisting of 4 students. The results of data analysis tests the physical condition of taekwondo athletes at SMA 1 Pangkalan Kerinci. Stating that the test results of the physical condition of male taekwondo athletes at SMA Negeri 1 Pangkalan Kerinci, in an endurance test with an average of 7.37, there were 1 sufficiently categorized athlete (6.40 - 7.27), and 3 athletes categorized as less (7.28 - 8.18), Flexibility Test with an average of 12, there are 2 well-categorized athletes (6-11), 1 sufficiently categorized athlete (12-17), and 1 athlete with less category (18-23), Speed test with an average of 4.81, there are 3 less category athletes (4.73 - 5.11), and 1 category athlete less once (5.12 - 5.50), Strength tests with an average of 24.5, there are 4 athletes in medium category (20-25), and agility tests with an average of 11.26, there are 4 athletes categorized as very good (> 12.10). Based on the results of the research review of the physical condition of the Male Taekwondo Athletes in SMA 1 Pangkalan Kerinci, there were 1 athlete categorized quite well, 2 Athletes in the Good category, and 1 Athletes in the Excellent category. So it can be concluded that the condition of the male taekwondo athlete at SMA 1 Pangkalan Kerinci is included in the Good category.Key Words: Physical Condition, Taekwondo Athletes